Clinical study of disseminated intravascular coagulation in pregnancy at tertiary care centre - risk factors, complications, management and outcome - Sarojini; Prathima S; Ashakiran Thavarsingh Rathod (Barpeta Obstetrics and Gynaecological Society, 2023)
Objectives: 1) To estimate the frequency of DIC in pregnant women admitted in Vanivilas hospital, 2) To describe the risk factors of DIC, 3) To describe the maternal and perinatal outcome. Methods: This is a prospective study conducted at Vanivilas Hospital, Bangalore, Karnataka, from January 2019 to June 2020 for 18 months. After applying inclusion criteria and DIC scoring from ISTH, 96 women who were diagnosed with overt DIC were studied with respect to their age, parity, presenting symptoms, associated obstetric complications, mode of delivery, number of transfusions, development of complications and maternal and perinatal outcome. Results: There were 23476 deliveries and 96 (1 in 245 deliveries) cases of overt DIC during 18 months period. Among associated obstetric complications, 40.6% had abruptio placenta, 26% pregnancy induced hypertension, 14.6% postpartum haemorrhage, 6.3% IUD, 5.2% HELLP syndrome, 4.2% AFLP and 3.2% suspected embolism. The complications of DIC noted were haemorrhage 75%, hypovolemic shock 40.6%, acute kidney injury 18.8%, MODS 37.5%, sepsis 18.6% and maternal deaths 12.5%. All 96(100%) women were admitted to ICU and all received blood component transfusions. 30.2% required mechanical ventilation, 18.8% ionotrope support, 16.7% dialysis, and 13.5% underwent peripartum hysterectomy and 11.5% stepwise devascularisation. 33.3% neonates required NICU admission and 27.1% were preterm births. Conclusion: DIC was seen in 1 in 245 deliveries. Abruption was the commonest risk factor for DIC. Obstetric haemorrhage was the main complication. The maternal mortality associated with DIC was 12.5%.